X-ray diffraction study on the orientation dynamics of biaxial microcrystals under static and rotating magnetic fields. Issue 28 (26th June 2019) - Kimura, F.; Horii, S.; Arimoto, I.; Notsu, D.; Doi, T.; Wada, M.; Kimura, T.
Abstract : The orientation of microcrystals of DyBa2 Cu3 O y ( y ~ 7) under static and rotating magnetic fields was studied. Abstract : The orientation of microcrystals of DyBa2 Cu3 O y ( y ~ 7) under static and rotating magnetic fields was studied. The suspension of the microcrystals was exposed to the static and rotating magnetic fields and their orientation process was monitored via in situ X-ray diffraction (XRD) measurements. Under the static magnetic field, the orientation process was characterized by a single time constant, indicating that the microcrystal is close to uniaxial. When the rotating magnetic field was applied, the two-dimensional XRD profile changed as a function of the rotation speed. The transition from the static profile to the rotating one was identified at a rotation speed ω θ . At about 10 × ω θ, the orientation of the hard-magnetization axis was completed.